Flow Conditioning to Control the Effects of Inlet Swirl on Brush Seal Performance in Gas Turbine Engines - Liu, Yuxin; Dong, Wenlei; Chew, John; Pekris, Michael; Yue, Benzhuang; Kong, Xiaozhi (Frontiers in Energy Research, 2022)
When subject to highly swirling inlet flow, the bristles on the upstream face of a brush seal in gas turbine engines tend to slip circumferentially, which may lead to aeromechanical instability and seal failure. In this article, a new design of the front plate of brush seal, which mitigates this effect, is presented. Angled ribs on the upstream side of the front plate are used to reduce the swirl of the flow impacting on the bristle pack. The effects of the rib geometry, including angle of inclination and height-to-spacing ratio, are investigated using computational fluid dynamics, and a bulk porous medium model of the bristle pack, on a simple seal geometry. Results show that the ribs can effectively regulate the flow upstream of the bristle pack, reducing the swirl and channeling flow radially inward to the sealing section, resulting in decreased circumferential forces on the bristles. Ribs inclined at 20° to the radial direction and with height-to-spacing ratio of 0.4 were selected as the most effective of those investigated for the seal geometry under study. A model of an aeroengine preswirled cooling air chamber was created to give insight into the inlet swirl boundary conditions that a preswirl seal brush seal could be subjected to at a range of leakage flow rates and inlet swirl velocities. The new design and upstream roughness feature substantially reduced inlet swirl velocity incident on the bristle pack. The findings in this work could have a significant impact on brush seal design and, in particular, mitigate a significant operational risk of swirl-induced instability in high-pressure, high-speed shaft seal locations.